Flood Detection and Mitigition System Using SMS Notifications - Ghazali, Muhamad Nabil Asyraf; Jamil, Ansar; Abdullah, Jiwa; Muhammad Audah, Lukman Hanif; Alias, Rozlan (Evolution of Information, Communication and Computing System, 2022)
The main causes of flood are hydrological condition, metrological condition, geographical condition, planning problem and environmental status due to human activity etc. [1]. Hydrological condition arises due to the discharge of heavy rain fall and the enormous water. The hydrological condition is directly and indirectly associated with the metrological condition such as heavy rainfall, cyclone and storm. The geographical condition is also a major factor for flooding condition, for example, altitude of the place. Lower is the altitude of a place; the water flows from the neighbouring higher altitude. The planning problem such as poor drainage, high siltation in river, breaching of the embankments, spilling of floodwaters over them, contribute to flooding situation. The environmental status due to human activity is a significant cause for flooding situation, for example, deforestation, different type of pollution and more buildings construction etc. [1]. Floods can have devastating consequences and can have effects on the economy, environment, and people. During floods (especially flash floods), roads, bridges, farms, houses and automobiles are destroyed. The environment also suffers when floods occurred [2].